The effect of tyres and a rubber track at high axle loads on soil compaction, Part 1: Single axle-studies - Ansorge, Dirk; Godwin, R. J. (Elsevier, 2007)
One option for ground drive systems with large harvesting equipment is to use rubber-belted tracks; however, little is known about the performance of these systems relative to appropriately sized pneumatic tyres. The effect of self-propelled wheels and a track with high axle loads (9–24 t) on soil compaction were studied. Soil displacement and soil density changes were assessed by embedding talcum powder lines as tracer into the soil during preparation. In addition, soil dry bulk density and penetrometer resistance were measured. The track with loads of both 10.5 and 12 t compacts the soil less than wheels at a 10.5 t load in both weak uniform and stratified soil. Towed implement wheels with a 4.5 t load caused similar soil displacement to the track with a load of 12 t. Tyre inflation pressure had a significant influence on soil parameters. To reduce compaction a larger overall diameter was found to be more beneficial than a wider tyre. This emphasised the importance of contact pressure and its distribution with respect to soil density changes. Total axle loads are less important than how these loads are distributed on the ground.